THE IMPORTANCE OF PERSONNEL PLANNING AND INFRASTRUCTURE IN SUPPORTING WORK EFFECTIVENESS AT AR-RAHMAN IT SMP LAREH SAGO HALABAN - Nova Nova; Januar Januar; Ulva Rahmi; Yusrawati Yusrawati (Yayasan Adra Karima Hubbi, 2025)
This study aims to emphasize the importance of staffing planning and facilities in improving work effectiveness at SMP IT Ar-Rahman Lareh Sago Halaban, in the field of education, work effectiveness is highly dependent on the availability of a competent workforce and adequate facilities. This research uses a qualitative approach with a case study method at SMP IT Ar-Rahman Lareh Sago Halaban. Data were obtained through interviews, observation, and document analysis. The results showed that good staffing planning, including recruitment, training and staff development, plays a significant role in improving the performance of teachers and school staff. In addition, adequate facilities, such as comfortable classrooms, well-equipped laboratories and other supporting facilities, are also very important for creating a conducive learning environment. The findings emphasize that integrated and sustainable planning in terms of staffing and facilities is key to improving work effectiveness at SMP IT Ar-Rahman Lareh Sago Halaban. Therefore, schools need to continuously improve efforts in planning and managing human resources and educational facilities to achieve optimal educational goals.